Mass Transfer From Nonaqueous Phase Organic Liquids in Water-Saturated Porous Media - Geller, J. T. (1993)
Results of dissolution experiments with trapped nonaqueous phase liquids (NAPLs) are modeled by a mass transfer analysis. The model represents the NAPL as isolated spheres that shrink with dissolution and uses a mass transfer coefficient correlation reported in the literature for dissolving spherical solids. The model accounts for the reduced permeability of a region of residual NAPL relative to the permeability of the surrounding clean media that causes the flowing water to partially bypass the residual NAPL. The dissolution experiments with toluene alone and a benzene-toluene mixture were conducted in a water-saturated column of homogeneous glass beads over a range of Darcy velocities from 0.5 to 10 m d(−1). The model could represent the observed effluent concentrations as the NAPL underwent complete dissolution. The changing pressure drop across the column was predicted following an initial period of NAPL reconfiguration. The fitted NAPL sphere diameters of 0.15 to 0.40 cm are consistent with the size of NAPL ganglia observed by others and are the smallest at the largest flow velocity.